Excitonic devices - Butov, L.V. (Superlattices and microstructures, 2017)
Indirect excitons can be controlled by voltage, can travel over large distances before recombination, and can cool down close to the temperature of semiconductor crystal lattice and below the temperature of quantum degeneracy. These properties form the basis for the development of excitonic devices with indirect excitons. In this contribution, we overview our studies of excitonic devices. We present traps, lattices, conveyers, and ramps for studying basic properties of cold indirect excitons – cold bosons in semiconductor materials. We also present proof-of-principle demonstration for excitonic signal processing devices.